Clinical relevance of Clostridium bacteremia: An 8-year retrospective study. (June 2020) - Stabler, Sarah; Titécat, Marie; Duployez, Claire; Wallet, Frédéric; Loïez, Caroline; Bortolotti, Perrine; Faure, Emmanuel; Faure, Karine; Kipnis, Eric; Dessein, Rodrigue; Le Guern, Rémi
Abstract: Clostridium spp. are recovered from 25% of the blood culture positive with anaerobes. However, the clinical relevance of Clostridium bacteremia has been controverted in the literature, particularly for C. perfringens . We aimed to evaluate the clinical relevance of Clostridium bacteremia, either due to C. perfringens or other Clostridium species, and to identify the risk factors of mortality in these patients. A retrospective cohort study was conducted from January 2010 to April 2018. All the patients with at least one blood culture positive with any Clostridium species were included. Eighty-one patients with a least one blood culture positive with any Clostridium species were included. Seventy patients (86.4%) fulfilled the criteria for clinically relevant bacteremia. Bacteremia due to C. perfringens tended to be less clinically relevant than other Clostridium species but this was not statistically significant (76% vs 91.2%, P  = 0.09). In case of clinically relevant bacteremia, the 30-day mortality rate was 31.4%. In multivariate analysis, adequate empiric antimicrobial therapy was significantly associated with survival ( P  = 0.03). In conclusion, bacteremia due to C. perfringens or other Clostridium species is usually clinically relevant. This finding was also supported by an improved survival at 30 days when adequate empiric antimicrobial therapy was administered. Highlights: Clostridium bacteremia is usually clinically relevant. Adequate empiric antimicrobial therapy improves the 30-day survival. Hypothermia is associated with increased mortality.